Manajemen Pembelajaran Berbasis Joyful Learning dan Implikasinya dalam Learning Revolution - I .M. Pastika (Pascasarjana Universitas Pendidikan Ganesha, 2023)
The present study aimed at comprehending the joyful learning basically and finding out the impact of joyful learning in learning revolution. This study was researching from home by collecting data about learning, fun learning, and learning revolution by exploring electronic books in Google Books and scientific articles in Google Scholar. This library research implemented four steps in its data collection, such as (1) recording all of the findings related to the research variables; (2) matching all of the findings related to the variables; (3) analyzing all the findings; and (4) criticizing, to get a new finding. The data collection technique of the study was documentation technique, namely reading, learning, analyzing, and recording literature related to the problem discussed. The data were collected through a resource called secondary data. Research instrument used was data card. Data analysis was conducted in two steps namely (1) analysis during data collection; and (2) analysis after the process of data collection. Validation of the data referred to the three categories such as trust, transferability, and legality. The results of this study proved that joyful learning is basically student centered, process emphasized, comprehensively facilitated, and effective. Theoretically, joyful learning can increase memory ability and practically it has impacts such as the innovation of joyful learning through game, humor, and song.